Disorder-induced gap in the normal density of states of the organic superconductor κ-(BEDT-TTF)2Cu[N(CN)2]Br. (15th June 2015) - Diehl, Sandra; Methfessel, Torsten; Tutsch, Ulrich; Müller, Jens; Lang, Michael; Huth, Michael; Jourdan, Martin; Elmers, Hans-Joachim
Abstract: The local density of states (DOS) of the organic superconductor -(BEDT-TTF)2 Cu[N(CN)2 ]Br, measured by scanning tunneling spectroscopy on in situ cleaved surfaces, reveals a logarithmic suppression near the Fermi edge persisting above the critical temperature . The experimentally observed suppression of the DOS is in excellent agreement with a soft Hubbard gap as predicted by the Anderson–Hubbard model for systems with disorder. The electronic disorder also explains the diminished coherence peaks of the quasi-particle DOS below .